AHLUL BAIT'S FIRST ARRIVAL IN INDONESIA AND THE EXPLORATION OF ISLAMIC HISTORY IN SOUTHEAST ASIA - Hidayat, Asep Achmad; Kusumawardhana, Gelar Taufiq; Kusdiana, Ading; Supendi, Usman; Hernawan, Wawan; Isnendes, Chye Retty (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
ABSTRACTThis research aims to explore the history of the arrival of the first wave of Ahlul Bait in Aceh-Sumatra. The wave will technically relate to the history of the founding of the earliest Islamic sultanates in the Aceh-Sumatra between the 8th and 9th centuries AD, such as the Jeumpa sultanate and the Perlak sultanate. The research is based on historical interpretation in the form of classical Acehnese and Malay manuscripts from tertiary historical sources. However, the research still leave problems in the detailed area which are not yet completely accurate and precise. So, even though we have found a common thread that can be mutually agreed upon, attention to areas of detail that are not yet completely accurate and precise, still needs to continue to be explored and its findings improved. As for the shortcomings, they can be remedied by reading the narrative interpretations of classical texts more holistically and coherently to produce narratives that are clearer and clearer in their construction, both in terms of chronology and in terms of interpretations of the agents or apparatus of the establishment of the sultanates.Keywords: ahlul bait, Jeumpa, Perlak, KedahÂ ABSTRAKPenelitian ini bertujuan untuk menelusuri sejarah kedatangan Ahlul Bait gelombang pertama di Aceh-Sumatera. Gelombang tersebut secara teknis akan berkaitan dengan sejarah berdirinya kesultanan Islam paling awal di Aceh-Sumatera antara abad ke-8 hingga ke-9 M, seperti kesultanan Jeumpa dan kesultanan Perlak. Penelitian ini didasarkan pada penafsiran sejarah berupa naskah klasik Aceh dan Melayu dari sumber sejarah tersier. Namun penelitian tersebut masih menyisakan permasalahan pada area detail yang belum sepenuhnya akurat dan tepat. Jadi, meski sudah menemukan benang merah yang bisa disepakati bersama, namun perhatian pada area detail yang belum sepenuhnya akurat dan tepat, masih perlu terus digali dan temuannya diperbaiki. Adapun kekurangannya dapat diatasi dengan membaca tafsir naratif teks klasik secara lebih holistik dan koheren sehingga menghasilkan narasi yang semakin jelas konstruksinya, baik dari segi kronologisnya maupun dari segi penafsiran pelaku atau aparaturnya. berdirinya kesultanan.Kata kunci: ahlul bait, Jeumpa, Perlak, Kedah